2017
DOI: 10.3390/biom7040079
|View full text |Cite
|
Sign up to set email alerts
|

Is Antimicrobial Photodynamic Therapy Effective as an Adjunct to Scaling and Root Planing in Patients with Chronic Periodontitis? A Systematic Review

Abstract: The aim of this systematic review was to investigate whether antimicrobial photodynamic therapy (aPDT) as either a primary mode of treatment or an adjunct to non-surgical treatment was more effective than scaling and root planing (SRP) alone in treating chronic periodontitis in terms of clinical attachment level (CAL) gain and probing depth (PD) reduction. The focused question was developed using the Patient, Intervention, Comparison, and Outcome (PICO) format, and two authors independently searched the Medlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…In this study, the presence and levels of A. actinomycetemcomitans , P. gingivalis , P. intermedia , T. forsythia , and T. denticola were investigated in the subgingival plaque samples obtained from the sites with initial PD ≥ 5 mm by using micro‐IDent® test. At baseline, microbiological profiles of the patients were consistent with studies examining the subgingival microflora of GAgP . In our study, despite A. actinomycetemcomitans was the least frequently encountered microorganism among the five periodontopathogens examined, P. gingivalis was detected in all subgingival plaque samples collected at baseline.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the presence and levels of A. actinomycetemcomitans , P. gingivalis , P. intermedia , T. forsythia , and T. denticola were investigated in the subgingival plaque samples obtained from the sites with initial PD ≥ 5 mm by using micro‐IDent® test. At baseline, microbiological profiles of the patients were consistent with studies examining the subgingival microflora of GAgP . In our study, despite A. actinomycetemcomitans was the least frequently encountered microorganism among the five periodontopathogens examined, P. gingivalis was detected in all subgingival plaque samples collected at baseline.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, the researchers suggested that a combination of both treatment methods would yield better results for the NPT of aggressive periodontitis. So, the use of PDT in the treatment of periodontal diseases is still an object of interest .…”
Section: Introductionmentioning
confidence: 99%
“…112 Due to its antibacterial effects, aPDT along with SRP is advantageous and effective in the treatment of periodontitis. 113 aPDT plus SRP resulted in a significant reduction in probing depth and a suppression of IL-1β and MMP-8 in GCF when compared with SRP alone 114 aPDT plus SRP also decreased the amount of periodontal pathogens (red and orange complexes) and lowered the IL-1β/ IL-10 ratio in GCF compared to SRP alone. 115 Compared with the systemic use of metronidazole, aPDT significantly lowered the bacterial load and IL-1β level of the gingival sulcus of rats with periodontitis.…”
Section: Antibioticsmentioning
confidence: 96%
“…[10] The singlet excited state PS molecules can be converted to a triplet excited state by intersystem crossing. [2,11,12] The PS triplet excited state transfer energy (type II reaction) or electron (type I reaction) to the oxygen molecule, with consequent formation of singlet oxygen or free radicals, respectively. [2,7,8,10] These oxidant species lead to toxic and destructive action in bacteria.…”
Section: Introductionmentioning
confidence: 99%